Clay mineral variations in Holocene terrestrial sediments from the Indus Basin - Alizai, Anwar; Hillier, Stephen; Clift, Peter D.; Giosan, Liviu; Hurst, Andrew; VanLaningham, Sam; Macklin, Mark (Quaternary Research, 2012)
We employed X-ray diffraction methods to quantify clay mineral assemblages in the Indus Delta and flood plains since ~ 14 ka, spanning a period of strong climatic change. Assemblages are dominated by smectite and illite, with minor chlorite and kaolinite. Delta sediments integrate clays from across the basin and show increasing smectite input between 13 and 7.5 ka, indicating stronger chemical weathering as the summer monsoon intensified. Changes in clay mineralogy postdate changes in climate by 5–3 ka, reflecting the time needed for new clay minerals to form and be transported to the delta. Samples from the flood plains in Punjab show evidence for increased chemical weathering towards the top of the sections (6–
id: 2333